Degradación del ensilaje del bagazo de caña de azúcar amonificado a distintos tiempos de fermentación como alimento del ganado bovino en época seca - Bravo Vargas, Ángel Ruisdael (2019)
Through this study it was possible to evaluate the degradation in situ of the silage of the ammonified sugarcane bagasse, as food for cattle in dry season. Samples of fresh sugarcane bagasse (Saccharum sp) from the “Puro Bravo” Farm, located at the “La Soledad” site, Junín canton, Manabí province, are randomly taken. A Completely Randomized Design with 3x2 Factorial Arrangement is found, where Factor A is represented by the different levels of urea inclusion (0, 3 and 5%) and Factor B, fermentation times of cane bagasse (30 and 44 days), each combination of these factors consisted of three repetitions. The best treatment is 5% urea, day 30 of fermentation, both in bromatology and degradability, in addition the degree of association of degradability at different times was related to the nutritional value of ammonified cane bagasse, which is related to degradability and fiber. Ammonification with urea improves nutritional values, varied by the increase in crude protein and decrease, as well as FDN, FDA and LDA as urea levels increase. The differences were highly significant (P <.0001). The above indicates that the results were highly significant for each of the variables studied, with which the degree of association of degradability at different times could be related to the nutritional value of ammonified cane bagasse silage.